A new species of Pachysvastra Moure & Michener (Hymenoptera: Apidae) discovered in Argentina - Alvarez, Leopoldo J.; Lucia, Mariano (Zootaxa, 2024)
A new species, Pachysvastra luquita, is described and figured from northeastern Argentina, which extends the range of the genus. An identification key for the three known species of Pachysvastra and updated occurrence records are given.